Financial Sector Regulation and Supervision : The Case of Small Pacific Island Countries - Riechel, Klaus-Walter (IMF Policy Discussion Papers; Policy Discussion Paper, 2001)
This paper discusses issues of financial sector regulation and supervision--including those concerning nonbank financial intermediaries--in small resource-constrained Pacific island countries. It advocates stronger cooperation in these areas and calls for increased financial and technical assistance. The paper also reviews recent international initiatives directed toward offshore financial centers and the fight against money laundering and other financial crime and explores their significance for the Pacific island countries.